2019
DOI: 10.1136/bmjopen-2018-025159
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of introducing a soft opt-out organ donation system in Wales: before and after study

Abstract: ObjectivesTo determine the short-term impact of a soft opt-out organ donation system on consent rates and donor numbers.DesignBefore and after observational study using bespoke routinely collected data.SettingNational Health Service Blood and Transplant.Participants205 potential organ donor cases in Wales.InterventionsThe Act and implementation strategy.Primary and secondary outcomesConsent rates at 18 months post implementation compared with 3 previous years, and organ donor numbers 21 months before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…This remains a considerable issue under opt‐out laws. In a recent study which analysed transplant data from Wales, a number of notable findings regarding family consent under opt‐out laws were reported (Noyes et al , ). The findings revealed that when an opt‐in decision was registered, 16.4% of families overrode their loved ones recorded decision and refused consent for donation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This remains a considerable issue under opt‐out laws. In a recent study which analysed transplant data from Wales, a number of notable findings regarding family consent under opt‐out laws were reported (Noyes et al , ). The findings revealed that when an opt‐in decision was registered, 16.4% of families overrode their loved ones recorded decision and refused consent for donation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 6% of the Welsh population have opted out of the donor register. It is noteworthy, however, that a recent analysis of routine transplant figures from Wales found that 16.5% of potential donors had expressed the decision to opt‐out of organ donation (Noyes et al , ). Only a small proportion of these individuals had actively registered their opt‐out decision, with the vast majority (76%) of individuals verbally expressing their opt‐out decision to family members.…”
Section: Introductionmentioning
confidence: 99%
“…The study was awarded a national prize for the co‐production element. The study provides new insights and understanding about implementation of a soft opt‐out system of organ donation from the perspective of family members and professionals (See Box for summary of empirical study results) …”
Section: Discussionmentioning
confidence: 99%
“…The study provides new insights and understanding about implementation of a soft opt-out system of organ donation from the perspective of family members and professionals (See Box for summary of empirical study results). 11,12 Co-production worked well but it was an expensive research cost both in terms of resources (putting on events and activities) and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation